STUDI NUZULUL QUR’AN DALAM KAJIAN AL-QUR’AN - Hasanah, Muizzatul (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2022)
That the Qur'an is the best and most updated holy book of all time which was given the main mandate to the Prophet Muhammad. through the Angel Gabriel with a very humanistic narration and meaning. The Qur'an as the book of Allah occupies the first and foremost position of all Islamic teachings and functions as a guide or guide for mankind to achieve happiness in life in this world and in the hereafter. The main purpose of the discussion of Nuzulul Qur'an Studies is as a tool to understand the events of the series of ways in which the Qur'an was revealed to the Prophet Muhammad, which will be followed and read throughout the ages. The results of the research on the study of Nuzulul Qur'an in the study of the Qur'an is that the process of the revelation of the Qur'an to the Prophet Muhammad SAW, which was revealed on the night of glory by the intermediary of the angel Gabriel, as a guide and guidance for mankind. As for the Prophet Muhammad SAW., it is as a power to increase the faith and strength of the soul and mental of the prophet whose end is the spaciousness of his soul, facilitating understanding and memorization so that the processes in conveying become more organized, showing that this is the best miracle that can be seen. and become evidence of apostolate and prophethood that are sensitive to time and time.